Fish, Fishing and Community in North Korea and Neighbours Vibrant Matter(s) - Winstanley-Chesters, Robert (Springer Nature, 2020)
This open access book explores the histories and geographies of fishing in North Korea and the surrounding nations. With the ideological and environmental history of North Korea in mind, the book examines the complex interactions between local communities, fish themselves, wider ecosystems and the politics of Pyongyang through the lens of critical geography, fisheries statistics and management science as well as North Korean and more generally Korean and East Asian studies. There is increasing global interest in North Korea, its politics, people and landscapes, and as such, this book describes encounters with North Korean fishing communities, as well as unusual moments in the field in the People's Republic of China, the Russian Federation and the Republic of Korea (South Korea). It addresses fish, fishing infrastructure, fishing science and fishing statistics and other non-human elements of North Korean and other nations' developmental regimes as actors and participants within them as much as humans and their technologies. The book enables readers to gain extensive insights into the aspirations and practices of fishing in North Korea and its neighbours, the navigation of difficult political and developmental situations and changing ecological realities in a time of environmental and climate crisis familiar to many across the globe.